Pelaksanaan Perjanjian Kerja Sama Tanah Ulayat Antara PT. Akasindo Hutan Rakyat Dengan Kelompok Tani Kenegerian Simandolak Jaya Kecamatan Benai Kabupaten Kuantan Singingi - PRIANDO MAHDELTA; Maryati Bachtiar; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The agreement is referred to as agreement or agreement, because theparties that make it certainly agree on the contents of the agreement made tocarry out certain achievements. In its form, the agreement is in the form of aseries of words that contain promises or abilities that are spoken or writtenbetween two or more people who are bound together. The will of the partiesembodied in the agreement is the basis for binding an agreement in Frenchcontract law. This will can be expressed in various ways both oral and writtenand binds the parties with all legal consequences. As is known, the French CivilCode affects Burgelijk Wetboek Netherlands, and subsequently based on theconcordance principle, Burgelijk Wetboek Netherlands is adopted in theIndonesian Civil Code.Agreement between PT. Akasindo Rakyat Forest with Simandolak JayaFarmers Group has reached an agreement in the deliberation, namely the PT.Akasindo will build rice field irrigation for the community within 3 months afterthe consultation. But in reality the agreement has not been realized by PT.Akasindo Hutan Rakyat even though the agreement has been running for 9 monthsafter deliberation. For this reason the author feels that PT. Aksindo Hutan Rakyatas the party who promised to be negligent from the agreement that had beenagreed upon, and the community felt that they had been disadvantaged, especiallythe people who were very hopeful of rice field irrigation, but until now they didnot get it.Direction to every Kenegerian Simandolak Jaya community to accept theresults with an agreement for regional development in Kenegerian SimandolakJaya. As well, PT. Akasindo Hutan Rakyat carried out the contents of theagreement that had been agreed with the Management of the KenegerianSimandolak Jaya Farmers Group so that the implementation of the cooperationcould run well and there would be no more problems arising between the twoparties.Keywords: Agreement - Implementation of Agreement - Ulayat Land